Strategi Kepala Sekolah Dalam Peningkatan Disiplin Kerja Guru - Nurti, Syafni; Hendriani, Suswati (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this discussion is to explain the leadership role of the school principal in Improving teacher Work Discipline. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. The analysis technique that the writer uses according to Miles and Huberman. The results of the study show the role in increasing the work discipline of educational staff, namely: as an educator the principal gives freedom and is firm to educational staff, as a manager the principal coordinates his subordinates so that they work to improve work discipline. As an Administrator the principal has administrative management activities that are recording, compiling and documenting, as a Supervisor that is carrying out supervision and control to improve work discipline through a familial approach. As a leader the principal guides, fosters, encourages and directs all parties in the school, and is able to accept criticism and suggestions from his subordinates. As an innovator the principal guides, fosters, encourages and directs all parties in the school, and is able to accept criticism and suggestions from his subordinates.